Pervasive Phylogenomic Incongruence Underlies Evolutionary Relationships in Eyebrights (Euphrasia, Orobanchaceae) - Garrett, Phen; Becher, Hannes; Gussarova, Galina; dePamphilis, Claude W.; Ness, Rob W.; Gopalakrishnan, Shyam; Twyford, Alex D. (Frontiers in Plant Science, 2022)
Disentangling the phylogenetic relationships of taxonomically complex plant groups is often mired by challenges associated with recent speciation, hybridisation, complex mating systems and polyploidy. Here, we perform a phylogenomic analysis of eyebrights (Euphrasia), a group renowned for taxonomic complexity, with the aim of documenting the extent of phylogenetic discordance at both deep and at shallow phylogenetic scales. We generate whole genome sequencing data and integrate this with prior genomic data to perform a comprehensive analysis of nuclear genomic, nuclear ribosomal (nrDNA), and complete plastid genomes from 57 individuals representing 36 species. The species tree analysis of 3454 conserved nuclear scaffolds (46 Mb) reveals that at shallow phylogenetic scales post glacial colonisation of North Western Europe occurred in multiple waves from discrete source populations, with most species not being monophyletic, and instead combining genomic variants from across clades. At a deeper phylogenetic scale, the Euphrasia phylogeny is structured by geography and ploidy, and partially by taxonomy. Comparative analyses show Southern Hemisphere tetraploids include a distinct subgenome indicative of independent polyploidy events from Northern Hemisphere taxa. In contrast to the nuclear genome analyses, the plastid genome phylogeny reveals limited geographic structure, while the nrDNA phylogeny is informative of some geographic and taxonomic affinities but more thorough phylogenetic inference is impeded by the retention of ancestral polymorphims in the polyploids. Overall our results reveal extensive phylogenetic discordance at both deeper and shallower nodes, with broad-scale geographic structure of genomic variation but a lack of definitive taxonomic signal. This suggests that Euphrasia species either have polytopic origins, or are maintained by narrow genomic regions in the face of extensive homogenising gene flow. Moreover, these results suggest genome skimming will not be an effective extended barcode to identify species in groups such as Euphrasia or many other postglacial species groups.